2008
DOI: 10.1016/j.envpol.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stream ecological integrity using litter decomposition and benthic invertebrates

Abstract: Biomonitoring programs to access the ecological integrity of freshwaters tend to rely exclusively on structural parameters. Here we evaluated stream ecological integrity using (a) benthic macroinvertebrate derived metrics and a biotic index as measures of structural integrity and (b) oak litter decomposition and associated fungal sporulation rates as measures of functional integrity. The study was done at four sites (S1, S2, S3 and S4) along a downstream increasing phosphorus and habitat degradation gradient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 41 publications
(50 reference statements)
6
41
0
11
Order By: Relevance
“…By contrast, decomposition rate in coarse-mesh bags was greater than that in fine-mesh bags in the flume without ELD. The magnitude of leaf litter decomposition rates in our study was similar to the range reported for other studies [7][8][9][10] . According to Gessner and Chauv [8] in Table2, the scores of decompostion rates are 2 in both fine-mesh bags and coarse-mesh bags, while the scores of decompsotion rates are 1 in both fine-mesh bags and coarse-mesh bags.…”
Section: Resultssupporting
confidence: 80%
“…By contrast, decomposition rate in coarse-mesh bags was greater than that in fine-mesh bags in the flume without ELD. The magnitude of leaf litter decomposition rates in our study was similar to the range reported for other studies [7][8][9][10] . According to Gessner and Chauv [8] in Table2, the scores of decompostion rates are 2 in both fine-mesh bags and coarse-mesh bags, while the scores of decompsotion rates are 1 in both fine-mesh bags and coarse-mesh bags.…”
Section: Resultssupporting
confidence: 80%
“…The chosen scenario was the case of a shallow lentic ecosystem situated next to drained fields under hydromorphic regime. Three routes of entry were simulated: drift (improved Ganzelmeier curves; Reichenberger et al 2008), drainage (MACRO;Larsbo and Jarvis 2003), and runoff (PRZM; Carsel et al 1984). Simulations were performed using meteorological data for three successive years exhibiting average pesticide fluxes (1997/1998/ 1999).…”
Section: Exposure Scenarios and Mesocosm Treatmentsmentioning
confidence: 99%
“…Small forest streams are also highly vulnerable to global warming because most of their biota have relatively low upper thermal tolerance limits (de Koz lowski & Bunting 1981, Eaton & Scheller 1996 and will lack thermal refugia if they are already at their high latitude or highland limit. Also, the hetero trophic nature of these small streams and their strong interaction with the terrestrial surroundings (Vannote et al 1980, Mulholland et al 2001) make them most sensitive to changes in the riparian vegetation, which can result from invasion by exotic species, conversion of diverse deciduous forests into tree monocultures or agricultural fields, vegetation re mo val by forestry practices or urban development (Chadwick et al 2006, Ferreira et al 2006b, Lecerf et al 2007, Castela et al 2008. All these threats have been shown to induce changes in the structure of aquatic communities (Bärlocher & Graça 2002, Pascoal et al 2005, Ferreira et al 2006b, Castela et al 2008, Dang et al 2009), which might have profound consequences for the maintenance of ecosystem processes.…”
Section: Introductionmentioning
confidence: 99%